1986
DOI: 10.1108/eb008164
|View full text |Cite
|
Sign up to set email alerts
|

Cannibalism in Multibrand Firms

Abstract: Although cannibalism is seldom desirable, it can be tolerated under certain conditions. This paper illustrates those conditions and shows that cannibalism may not be so bad after all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…These effects can called product cannibalism". A similar definition is stated by Traylor (1986): cannibalism occurs when sales of a product from a company reduce sales of other. Traylor notes that cannibalism is a problem faced primarily by companies that use multi-brand strategies, since the risk of cannibalism increases as they seek better definitions of new market segments.…”
Section: Cannibalism In Marketingmentioning
confidence: 99%
See 3 more Smart Citations
“…These effects can called product cannibalism". A similar definition is stated by Traylor (1986): cannibalism occurs when sales of a product from a company reduce sales of other. Traylor notes that cannibalism is a problem faced primarily by companies that use multi-brand strategies, since the risk of cannibalism increases as they seek better definitions of new market segments.…”
Section: Cannibalism In Marketingmentioning
confidence: 99%
“…To prevent the occurrence of cannibalism is to introduce different products to well-defined market segments (Traylor, 1986;Copulsky, 1976). Kein et al (1978) identified that it was quite common in organizations that can cause cannibalism without benefits.…”
Section: Management Marketing Cannibalismmentioning
confidence: 99%
See 2 more Smart Citations
“…Primarily they raise the problem of cannibalization between new and remanufactured products. "...Cannibalism occurs when the sale of some of a company's portfolio of products reduces the sale level of one or more products in the company's portfolio of products" [25].…”
Section: Playersmentioning
confidence: 99%